The Cost of Coercion : Global Report Under the Follow-Up to the ILO Declaration on Fundamental Principles and Rights at Work, 2009. - Office, International Labour (International Labour Office, 2009)
Global Report under the follow-up to the ILO Declaration on Fundamental Principlesand Rights at Work, 2009. International Labour Conference, 98th Session 2009,Report I (B).